KERALA Politics of Pressure Groups - M K DAS (Economic and Political Weekly August 2, 2003, 2003)
Chief minister Antony's critical remarks about the pressure tactics of organised minorities in Kerala were provoked by the Muslim League's demands on the rehabilitation of the victims of communal violence in the fishing village of Marad and the stand of the Christian managements of two self-financing medical colleges in the matter of admissions and fees. While Karunakaran's predictable effort to use the episode to launch a revolt against the chief minister has been put down, thanks to the firm stand taken by the party high command, what Antony has to demonstrate in the three years he has left in power is his ability to successfully ride out the pressure politics of pressure groups without surrendering to them